Impact of Polypharmacy, Drug-Related Problems, and Potentially Inappropriate Medications in Geriatric Patients and Its Implications for Bulgaria—Narrative Review and Meta-Analysis - Krustev, Tzvetan; Milushewa, Petya; Tachkov, Konstantin (Frontiers in Public Health, 2022)
Objective. Polypharmacy and inappropriate prescribing are an overlooked issue in Bulgaria. We aimed at collecting and analysing global literature on the most prevalent risk factors and investigating what they could reveal about current practice. Materials and Methods. A systematic narrative review and meta-analysis was conducted on the topic, investigating the prevalence of polypharmacy, odds of potentially inappropriate medications (PIMs) due to polypharmacy, as well as the likelihood of developing a drug-related problem (DRP) due to PIMs. The results were then related to current demographic statistics to estimate the potential impact on Bulgarian elderly patients. Results. Prevalence of polypharmacy was estimated at 41% in elderly populations. The odds of a potentially inappropriate medication being prescribed were 2.095, with an expected 30.84% of those leading to a DRP. These numbers indicated that the expected Bulgarian elderly with polypharmacy should be 709 676 with 212 903 cases of DRPs. Conclusions. Global polypharmacy rates seem to be on the rise, with expected increases in DRPs.